THTHE INFLUENCE OF DESCRIPTIVE FACTORS ON COMPANY’S’ WEB PAGE INFLUENCE OF DESCRIPTIVE FACTORS ON COMPANY’S’ WEB PAGE - Jaharadak, Adam Amril bin; shukri, Sakinah mohd; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this paper is to determine the availability of descriptive factors in the company’s web page. Descriptive factors are the type of top-level domain name, information on authorship, availability of keyword, availability of description and currency of the website which are derived from the last date of modification.